Tumor Suppressor FBXW7 and Its Regulation of DNA Damage Response and Repair - Lan, Huiyin; Sun, Yi (Frontiers in Cell and Developmental Biology, 2021)
The proper DNA damage response (DDR) and repair are the central molecular mechanisms for the maintenance of cellular homeostasis and genomic integrity, whereas abnormality in this process is an important contributing factor to cancer development. FBXW7 is an F-box protein serving as the substrate recognition component of SCF (SKP1-CUL1-F-box protein) E3 ubiquitin ligase. By selectively targeting many oncoproteins for proteasome-mediated degradation, FBXW7 acts as a typical tumor suppressor. Recent studies have demonstrated that FBXW7 also plays critical roles in the process of DDR and repair. In this review, we first briefly introduce the processes of protein ubiquitylation by SCFFBXW7, and DDR/repair, then provide an overview of the molecular characteristics of FBXW7. We next discuss the role of FBXW7 in regulating DDR and repair. Finally, we propose few future perspectives to further elucidate the role of FBXW7 in regulation of a variety of biological processes and tumorigenesis, and to design a number of approaches for FBXW7 reactivation in a subset of human cancers for effective anticancer therapy.